2019
DOI: 10.3389/fpls.2019.01528
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Similarities in Flower Characteristics Between Novel Winter-Hardy Hibiscus Hybrids and Their Tropical Relatives

Abstract: Herbaceous winter-hardy Hibiscus spp. in the section Muenchhusia, also known as rosemallows, are attractive ornamental plants found in temperate environments. These should not be confused with woody winter-hardy hibiscus (Hibiscus syriacus L. and related species) which have also been intensively used as ornamental shrubs. During the past 70 years, breeders have attempted to create winter-hardy hibiscus hybrids with novel flower colors resembling the distantly related tropical Chinese hibiscus, Hibiscus rosa-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Other promoter and various factors could modify chemical components including soil, fertility, pH, temperature, humidity and other stresses ( Kandhare et al, 2012 , Da-Costa-Rocha et al, 2014 ). Previously Malinowski et al, 2019 , Chou et al, 2019 , reported that the EO production depends on the seasonal variation and various environmental factors. It also increases the common volatile compounds natures due to the stress condition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other promoter and various factors could modify chemical components including soil, fertility, pH, temperature, humidity and other stresses ( Kandhare et al, 2012 , Da-Costa-Rocha et al, 2014 ). Previously Malinowski et al, 2019 , Chou et al, 2019 , reported that the EO production depends on the seasonal variation and various environmental factors. It also increases the common volatile compounds natures due to the stress condition.…”
Section: Resultsmentioning
confidence: 99%
“…Among the various parts of HRS, the petals, flowers and seeds are frequently produced more therapeutic advances such as antibacterial, antifungal, antiviral, anticancer, larvicidal, antidiabetics, antioxidant properties ( Kartinah et al, 2019 , Lingesh et al, 2018 , Maralit Bruan and Tianco, 2019 , Elemar Gomes et al, 2010 , Gandhi et al, 2019 ). In addition, antihypertensive, anti-inflammatory, antipyretic, antidiarrhoeic and immunomodulator properties of the HRS have been screened from various pharmaceutical industry ( Begum and Younus, 2018 , Abdullah et al, 2019 , Malinowski et al, 2019 , Eman et al, 2018 , Rubini et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Shifting shadow from sun or light. The tubing is thriving on daily irrigation, although it is optional since it is very resistant to drought and is easy to root gulzuba [56].…”
Section: Hibiscus Mutabilis (Gulzuba)mentioning
confidence: 99%
“…Since anthocyanin-3-sambubioside aggregation shifts the flower's color in red by late afternoon [58]. Phenylalanine ammonia-lyase production (PAL) in petals is steadily increasing to 7 times their initial level at the start and during the fast accumulation process, and then decreases during floral senescence [56]. The synthesis of anthocyanin thus depends on the de novo cinnamic acid production.…”
Section: Hibiscus Mutabilis (Gulzuba)mentioning
confidence: 99%
“…The genus Hibiscus has more than 250 species, including annual and perennial herbaceous forms and ending with small woody shrubs [1]. Representatives of various species of the genus Hibiscus, due to their attractiveness, are used for landscaping for various purposes, including in coastal areas with a high salt content, and some species are used as raw materials for the preparation of medicines [2][3][4].…”
Section: Introductionmentioning
confidence: 99%